2015
DOI: 10.1016/j.cub.2015.02.022
|View full text |Cite
|
Sign up to set email alerts
|

PLETHORA Genes Control Regeneration by a Two-Step Mechanism

Abstract: SummaryBackground-Regeneration, a remarkable example of developmental plasticity displayed by both plants and animals, involves successive developmental events driven in response to environmental cues. Despite decades of study on the ability of the plant tissues to regenerate complete fertile shoot system after inductive cues, the mechanisms by which cells acquire pluripotency and subsequently regenerate complete organs remain unknown.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
304
2
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 245 publications
(323 citation statements)
references
References 44 publications
15
304
2
2
Order By: Relevance
“…We also confirmed the previously reported upregulation of PLT1, 2, 3, 5, and 7 and CUC2 in explants cultured on CIM (Kareem et al, 2015) but found that none of their activation requires functional ESR1 ( Figure 7B). …”
Section: The Wind1-esr1 Pathway Is Required For Shoot Regeneration Insupporting
confidence: 92%
See 2 more Smart Citations
“…We also confirmed the previously reported upregulation of PLT1, 2, 3, 5, and 7 and CUC2 in explants cultured on CIM (Kareem et al, 2015) but found that none of their activation requires functional ESR1 ( Figure 7B). …”
Section: The Wind1-esr1 Pathway Is Required For Shoot Regeneration Insupporting
confidence: 92%
“…Accordingly, many regulators of lateral root development, including ABERRANT LAT-ERAL ROOT4, AUXIN RESPONSE FACTOR7 (ARF7), ARF19, LATERAL ORGAN BOUNDARIES DOMAIN16 (LBD16), LBD17, LBD18, and LBD29, are required for callus formation on CIM (Sugimoto et al, 2010, Fan et al, 2012, Ikeuchi et al, 2013. A recent study has demonstrated that additional regulators, PLETHORA3 (PLT3), PLT5, and PLT7, are also needed to make CIM-induced callus pluripotent (Kareem et al, 2015). Key players acting downstream of PLT3, PLT5, and PLT7 to confer pluripotency are PLT1 and PLT2, which are also known for their role in root meristem development (Aida et al, 2004;Galinha et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that additional reprogramming processes are required. PLT1 and PLT2 have been shown to be required to establish pluripotency during de novo shoot regeneration (Kareem et al, 2015). Our results show that during de novo root formation, PLT1 and PLT2, in combination with SHR, could also be involved in specification of root founder cells, which are pluripotent.…”
Section: Specification Of Root Founder Cellsmentioning
confidence: 62%
“…In addition, persistent expression of PLT1, PLT2, and SHR appears to be necessary during subsequent formative stages to maintain primordia growth, as the very primordia found in shr-2 plt1-4 plt2-2 quickly differentiate. In contrast, in the de novo shoot regeneration system, transient induction of PLT2 has been shown to be sufficient to specify shoot progenitors, whereas subsequent expression of other regulators is required to accomplish de novo shoot formation from these progenitors (Kareem et al, 2015).…”
Section: Specification Of Root Founder Cellsmentioning
confidence: 97%